Configuration and tuning GPFS for digital media environments - Lascu, Octavian (IBM redbooks., 2005)
In today's environments, when access to information is more and more demanding, media companies are implementing new solutions for their environments, focusing on performance, availability, and cost. Because GPFS historically comes from multimedia roots, the adoption of this product for digital media environments comes as a natural evolution. This IBM® Redbooks® publication focuses on the newest GPFS functionality and its on demand characteristics related to (but not limited to) digital media environments. Digital media information flow and requirements are analyzed and matched with GPFS functionality. Interoperability of a GPFS cluster and file sharing applications for Windows clients are discussed. This book presents a nine-step approach for configuring a GPFS cluster, and also presents various tools and techniques that make it easier for a systems administrator in GPFS implementation and day-to-day management tasks.